2004
DOI: 10.1037/1072-5245.11.4.305
|View full text |Cite
|
Sign up to set email alerts
|

Work-home interference, job stressors, and employee health in a longitudinal perspective.

Abstract: The purpose of the present longitudinal study was to examine the role of negative work-home interference (WHI) in the classical stressor-strain sequence. First, the predominant time-lagged path between WHI and job stressors was investigated. Furthermore, the direct and indirect (mediating) process of WHI, job stressors, and employee health was examined. The sample consisted of 383 health care employees. Results showed evidence for predominant time-lagged paths from Time 1 job stressors to Time 2 WHI and not th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
52
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 40 publications
(72 reference statements)
11
52
1
3
Order By: Relevance
“…Our main analyses were based on complete data available from 123 respondents (the respondent group). These response rates are comparable to those in similar mail surveys of employee samples (e.g., Houkes, Janssen, de Jonge, & Bakker, 2003;Parkes & von Rabenau, 1993) and in a 1 year longitudinal study of employees at residential care institutions for the elderly in the Netherlands (Peeters, de Jonge, Janssen, & van der Linden, 2004). It is noteworthy that much of the sample loss in the present study (and in other similar studies, see Tekleab, Takeuchi, & Taylor, 2005) was caused by employees who were no longer working at the institutions 2 years after the initial assessment.…”
Section: Response and Sample Characteristicssupporting
confidence: 78%
“…Our main analyses were based on complete data available from 123 respondents (the respondent group). These response rates are comparable to those in similar mail surveys of employee samples (e.g., Houkes, Janssen, de Jonge, & Bakker, 2003;Parkes & von Rabenau, 1993) and in a 1 year longitudinal study of employees at residential care institutions for the elderly in the Netherlands (Peeters, de Jonge, Janssen, & van der Linden, 2004). It is noteworthy that much of the sample loss in the present study (and in other similar studies, see Tekleab, Takeuchi, & Taylor, 2005) was caused by employees who were no longer working at the institutions 2 years after the initial assessment.…”
Section: Response and Sample Characteristicssupporting
confidence: 78%
“…The effort-recovery (E-R) model (Meijman & Mulder, 1998) has been used in recent studies to explain the mediating role of WIF in the relationship between work characteristics (e.g., work hours and job demands) and well-being (e.g., Geurts, Kompier, Roxburgh, & Houtman, 2003;Janssen, Peeters, de Jonge, Houkes, & Tummers, 2004;Peeters, de Jonge, Janssen, & van der Linden, 2004). The E-R model facilitates understanding of the impact of work stressors on well-being by considering the psychobiological processes that underlie this relationship .…”
Section: Introductionmentioning
confidence: 98%
“…The reverse causation approach has received very little attention until now (Peeters, de Jonge, Janssen, & Van der Linden, 2004), as inter-role interaction is generally considered as an outcome variable rather than predictor (Innstrand, Langballe, Espnes, Falkum, & Aasland, 2008). A recent meta-analysis showed that work-family conflict predicted work-related strain and that strain predicted work-family conflict over time, although both types of lagged effects were rather small (Nohe, Meier, Sonntag, & Michel, 2015).…”
Section: Reversed Effectsmentioning
confidence: 99%